Psychometric assessment of young visitors at the National Museum of Malaysia / Mohd Halim Mahphoth ... [et al.] - Mahphoth, Mohd Halim; Sulaiman, Zuraidah; Koe, Wei-Loon; Kamarudin, Nur Asyikeen; Dirgantari, Puspo Dewi (Universiti Teknologi MARA, 2021)
Museums have become an important institution for learning activities especially for young visitors as it provides significant function towards educational benefits and knowledge enrichment. The actual outcomes from learning experience need to be encountered in order to indicate satisfying experience level from museum visiting. However, the assessment of satisfying experience on museum visit is entirely lacking in the existing literatures. Therefore, this study proposes a set of assessment for young visitors in order to evaluate their satisfying experiences in museum. The items were adapted and developed from the concept of satisfying experiences established by museum practitioners. This paper aims to present evidence in order to show the validity of the survey data and the instrument meets the requirements of specific measurements as determined by Rasch model. It is hoped that the assessment of satisfying experience will benefit researchers as well as practitioners and educators in managing the quality of young visitors experience in museum. The literature also intends to add to the body of knowledge in museum context.